Considerações sobre a gestão de resíduos sólidos em instituições de ensino superior brasileira - Oliveira, Daniela Lemos (2023)
The issue of solid waste generation is a social problem that is also present in universities and needs a correct destination so that it does not cause negative social, environmental and economic impacts. This text presents a discussion about the issue of solid waste in view of the recent Federal Law No. 12.305/2010, National Solid Waste Policy (NSWP), regarding the proposal of instruments for management in Public Institutions and how this confrontation has taken place. in Higher Education Institutions (HEIs). HEIs generate a considerable volume of waste in their operations and they are responsible for applying measures for the correct handling of waste produced, as required by law. Therefore, this research aims to analyze the solid waste management plan of some Brazilian HEIs. Regarding the methodology, five institutions were selected, one from each Brazilian region, institutions that have a solid waste management plan, an analysis of these plans will be carried out, what they have in common or not. From this, a reflection will be made on the Brazilian scenario with regard to solid waste management in HEIs and the difficulties of implementing and executing a solid waste management plan in HEIs, pointing out the benefits of the HEI having NSWP.